INDIGENOUS GARMENTS AND ACCESSORIES OF THE G’ADDANG IN BARANGAY NGILEB: DOCUMENTATION ON PRODUCTION - Angela Garra (Lembaga Penelitian Universitas Pasundan, 2016)
This study was undertaken to document the production of indigenous garments and accessories of the Gaddang in Barangay Ngileb in Alfonso Lista, Ifugao to help preserve the culture in making such products. Using qualitative research, it explored the different product-making procedures by using the method of focus group discussion (FGD) or interview with photo-video documentation and actual observation to analyze information from five female respondents. With the results of the study, the following were gathered: main processes involved are weaving, cutting, sewing and bead designing. Tools they use are traditional and it is operated manually. It depends on what product and availability of the raw materials on how long it takes to finish. Gaddangs produce other products like cellphone cases, pen holder and bags. With the use of other resources like carabao horns, wild pig fangs, chicken feathers and kugon grass are also utilized, but other resources like fabric, beads and cotton threads are bought outside their community. They still have their beliefs, and colors they use are dominantly red inorder for them to be distinguished among others. They use quality threads inorder to maintain the best quality they have. And with just a little profit they gain, it is use to supplement their needs like foods, and other school finances for their children. And preserving this culture through this way, it will be of great benefit for the Gaddangs.